2017
DOI: 10.22438/jeb/38/5(si)/gm-05
|View full text |Cite
|
Sign up to set email alerts
|

The effect of naphthalene acetic acid and some rooting media on rooting abilities and shoot growth of Dwarf Nerium cuttings

Abstract: Aim: To evaluate the effect of different rooting media and naphthalene acetic acid on rooting abilities and shoot growth of Nerium oleander .Methodology: Petite Red and Petite Salmon (Dwarf Nerium), the experiment was designed randomly to obtain data from three replicates (ten cuttings per replicate). The cuttings taken during mid February were -1 rooted at different concentrations of NAA (500 and 1000 mg l ) and in growth media (peat, per lite and municipal sewage sludge) for 45 days. The shoot length and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…From Table 1, it follows that a growth regulator most frequently used for the rooting of cuttings is IBA. Multiple studies [29,34,48,49], however, have produced results that, like ours, indicate that NAA either alone or in combination with IBA has a better influence on rooting. On the other hand, although the results of our comparisons of IBA at different concentrations showed greater success in rooting cuttings using mid-and higher-IBA concentrations, some other studies have shown lower concentrations to be more favorable [32,33,44].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…From Table 1, it follows that a growth regulator most frequently used for the rooting of cuttings is IBA. Multiple studies [29,34,48,49], however, have produced results that, like ours, indicate that NAA either alone or in combination with IBA has a better influence on rooting. On the other hand, although the results of our comparisons of IBA at different concentrations showed greater success in rooting cuttings using mid-and higher-IBA concentrations, some other studies have shown lower concentrations to be more favorable [32,33,44].…”
Section: Discussionsupporting
confidence: 58%
“…There are many methods of vegetative propagation of woody plants [22,27], including by means of rooted cuttings, which is affected by multiple factors [28]. This approach has continued to develop and is used particularly in growing cultivars of fruit and ornamental woody plants [29][30][31][32][33][34]. In forestry, it is important to maintain the uniformity of genetically significant characteristics, especially in establishing plantations of fast-growing woody species [24,28,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the exogenous application of NAA for high root formation was also reported in stem cuttings of Vinca minor ( Zongqin & Jinxiang 1995 ), Mondia whitei ( Zobolo et al . 2009 ), Nerium oleander ( Akat et al . 2017 ) and Nerium odorum ( Kumar et al .…”
Section: Discussionmentioning
confidence: 99%